Pengaruh Kecenderungan Adiksi Media Sosial Tiktok Ttrhadap Fear Of Missing Out - Rahadiani, Salma Alisha Rahadiani; Muthahharah Thahir, Muthahharah Thahir; Julius, Andre Julius (Ma'soem University, 2025)
TikTok social media is now one of the most widely used applications by teenagers. Excessive use can cause addictive behavior and have an impact on students' psychological conditions, one of which is Fear of Missing Out (FoMO). FoMO is a feeling of fear of being left behind by trends or social activities that occur on social media, thus encouraging individuals to continue to be digitally connected. This study uses an inferential quantitative method, which aims to analyze the influence of TikTok social media addiction tendencies on FoMO in grade XI students at SMK Bakti Nusantara 666. Data were obtained through questionnaires and analyzed using descriptive statistics and simple linear regression. The results showed that out of a total of 198 students, 96 students were in the high addiction category and 14 students were in the low category. Meanwhile, for the FoMO category, 89 students were in the high category and 16 students were in the low category. The results of the regression test obtained a coefficient of determination (R Square) of 0.580, which means that the significant influence that TikTok social media addiction contributes 58% to FoMO in students. This shows a significant and positive influence between excessive use of TikTok and the emergence of social anxiety in students.